PENYULUHAN MANFAAT PENUNDAAN PEMOTONGAN TALI PUSAT PADA BAYI KEPADA IBU HAMIL - Mutiara Dwi Yanti; Nurul Aini Siagian; Vitrilina Hutabarat; Gf Gustina Siregar; Purti Ayu Yessy Ariescha; Andayani Boang Manalu (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The main causes of neonatal mortality are prematurity, complications related to childbirth, namely asphyxia and infections and birth defects. When in the womb, the baby's body system depends on the mother. At this time the fetus will get oxygen from the mother. When the baby is born into the world, then the umbilical cord is cut, automatically the dependence on the mother stops. Whether or not the function of the organs is measured by an assessment or test called the APGAR test. Assessment of the general condition of the baby is assessed one minute after birth and then 5 minutes after the baby is born. The World Health Organization (WHO) itself is now issuing guidelines related to clamping and cutting of the newborn's umbilical cord. A delay in clamping of the umbilical cord of more than 120 seconds is recommended to improve the degree of LBW health and nutrition in the baby. Central delay can improve the APGAR value in infants and affect hemoglobin (Hb), hematocrit (Ht) levels, increase blood volume or erythrocytes, so as to prevent hypovolemia and hypotension in low birth weight. However, this has not been widely socialized to pregnant women, especially in the third trimester. which is nearing labor. The purpose of this activity is to provide education to pregnant women about the importance of delaying the clamping of the baby's cord during childbirth. The method of implementing this activity is socialization to pregnant women about delaying cord clamping to prevent asphyxia in newborns.